The Location of Conjunctivochalasis and Its Clinical Correlation with the Severity of Dry Eye Symptoms - Dalianis, Georgios (Medicines (Basel), 2018)
Background: We aimed to investigate the clinical importance of conjunctivochalasis (CCH) and, further, to implement a new CCH classification system. Methods: 60 eyes of patients with whom, upon clinical examination, CCH was diagnosed were investigated for the presence of symptoms and signs characteristic of dry eye. The eyes were grouped based on two stages of severity, Stage 1 (minimal/mild) and Stage 2 (medium/severe), for each nasal, middle, and temporal position, and on the extent of CCH folds in each site. Results: In 40 (66.6%) out of 60 eyes, symptoms and signs of CCH were manifest: pain in 25 (41.6%), epiphora in 25 (41.6%), and lacrimal punctum obstruction from conjunctival folds in 22 (36.6%) eyes. Depending on the position of CCH, a greater percentage of symptoms appeared in Stage 2 in the nasal position (78.9%), followed by middle (68.7%) and temporal positions (60%). When TBUT values were compared, statistically significant differences were found proportional to grading (p < 0.001) and position (nasal more severe than temporal, p < 0.001), and such differences were also found when TBUT values of all eyes were compared with those of symptomatic eyes (p = 0.01) and with those of symptom-free eyes (p = 0.002). Conclusions: CCH is a rather frequent and commonly unrecognized condition that should always be considered in differential diagnoses of dry eye.